Reduction of implantation-induced point defects by germanium ions in n-type 4H-SiC - Sledziewski, Tomasz; Ellrott, Günter; Rösch, Willi; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2015)
We have investigated the electrical properties of germanium-implanted n-type 4H-SiC epitaxial layers. Deep level transient spectroscopy (DLTS) was employed in order to study the influence of germanium ions on implantation-induced point defects. In particular, we observe a decrease of the concentration of Z1/2 defect with increasing dose of implanted germanium.
UnivIS-Import:2017-12-18:Pub.2015.nat.dphy.IAP.LAP.reduct
Keywords: 4H-SiC; DLTS; Ion implantation; Point defects